Evolutionary conserved pathway of the innate immune response after a viral insult in Paracentrotus lividus sea urchin. (2nd April 2019) - Chiaramonte, Marco; Arizza, Vincenzo; Russo, Roberta
Abstract: Despite the apparent simplicity of the body organization of echinoderms, their immune system is competent to perform a complex innate immune response, which is far from being well understood. The echinoderms represent the most advanced invertebrates that form a bridge with the primitive chordates. In fact, they possess numerous receptors and effectors that are used to obtain a fast immune response. After an infection, the humoral and cellular immune response determines a network in which the main protagonists are membrane and endosomal receptors. The recognition of nonself molecules by specific membrane receptors triggers the immune response, stimulating consecutive intracellular events. We have previously shown how the polyinosinic–polycytidylic acid (polyI:C) that mimics a viral infection is able to induce an immune response in the sea urchin Paracentrotus lividus immune cells. It activates a specific membrane receptor belonging to the Toll‐like receptor (TLR) family. Here, we show the activated expression pattern of some genes involved in the downstream cascade of TLR signalling pathway, such as Pl‐Tbk and Pl‐Irf, whose partial sequence was isolated from P. lividus immune cells. Their mRNA expression increases consequentially to the polyI:C stimulation and in a temporal way. In addition, we analysed the expression of Pl‐NF‐kB and we found that its upregulation was time‐dependent, preceding Pl‐Tbk and Pl‐Irf increase. Protein analysis showed that also some cytokine (TNF‐α and IL‐1α) expression increased after polyI:C insult. Therefore, the purpose of this study was to discover the molecular mechanisms of the innate defence strategies, similarly to vertebrates, implemented by the sea urchins in order to cope with viral infection challenge.